Pengaruh Model Pembelajaran Learning Cycle 7E Pada Materi Larutan Penyangga Terhadap Hasil Belajar Siswa Kelas XI SMA N 2 Langowan - Elra Vira Repi; Ni Wayan Suriani; Freetje Waworuntu (Chemistry Department, Universitas Negeri Manado, 2019)
The many theories, formulas, and elements that must be memorized make chemistry subjects considered complicated especially if it is not accompanied by the selection of an appropriate learning model, it certainly affects the student learning outcomes. This study aims to determine the effect of the Learning Cycle 7E learning model on buffer material on the learning outcomes of Class XI students of SMA N 2 Langowan by using independent variables (Learning Cycle 7E) and dependent variables (learning outcomes). The research sample is students of Class XI MIPA 1 and XI MIPA 2 in SMA N 2 Langowan, the sample is determined by the Simple Random Sampling technique. The research method used is Quasi Experiment Design with Posttest-only Control Group Design research design. Testing of research instruments (post test) consists of validity and reliability tests. Data analysis method uses homogeneity test, normality test and t-test. Based on the analysis of the data it was found that the sample was homogeneous and normally distributed, t-test data at the real level (α) = 0.05 was obtained tcount = 9,489 and ttable = 2,042. Because tcount> ttable, reject H0 and H1 are accepted. Based on the results of the study concluded that there was an influence of the Learning Cycle 7E learning model on the buffer solution material on the learning outcomes of Class XI students of SMA N 2 Langowan with an average learning outcome in the experimental class 80.00 and the control class 35.59.